The relationship between environmental disclosure quality and earnings quality: a panel study of an emerging market. Issue 2 (21st March 2019) - Alipour, Mohammad; Ghanbari, Mehrdad; Jamshidinavid, Babak; Taherabadi, Aliasghar
Abstract : Purpose: The purpose of this paper is to examine the association between corporate environmental disclosure quality (EDQ) and earnings quality (EQ). Design/methodology/approach: The paper uses earnings persistence and accruals quality as a measures of EQ. The paper also uses panel data regression to examine the association between EDQ and EQ for a sample of 107 Iran non-financial firms. Two different theoretical frameworks are used to clarify whether and to what extent an association may exist as an explicit relationship between EDQ and EQ. Findings: After controlling for several firm-specific characteristics, the results show that between 2011 and 2016, there has been a significant positive relationship between EDQ and EQ. Practical implications: This study sheds light on the relevance of regulating corporate reporting within a setting where companies are already voluntarily reporting on environmental information. Findings have implications for policymakers who have mandated or considering mandating environmental reporting. To the policymakers, in particular, this study highlights the need for incorporating, within the listing rules, minimum requirements in relation to the nature and content of environmental reports. Social implications: The findings have implications for stakeholders in terms of effective information quality. The findings are important as more environmentally responsible firms may provide higher quality, more reliable and more transparent information to meet the ethical expectations of stakeholders. Originality/value: This is the first study in Iran that considered the impact of EDQ on EQ. This study contributes to the literature on the relationship between EDQ and EQ by showing that the EDQ in Iran is associated with the EQ.